DEVELOPING MODEL OF SCHOOL PRINCIPALS’ PERFORMANCE ASSESSMENT MANAGEMENT OF JUNIOR HIGH SCHOOL BASED ON COMPETENCE IN SURAKARTA (The Journal of Educational Development, 2015)
The implementation of school principals’performance assessment of Junior High Schools (SMP)in Surakarta has not been managed in accordance with the management functions of performance assessment, namely: the function of planning, organizing, implementing and monitoring. The statements of the problem in this study are: 1. what kind of management of principals’performance assessment (MPKKS) in Surakarta that has been implemented in Surakarta? 2. how is the model design of MPKKS based on competence in Surakarta? 3. How isthe MPKKS final model based on competency in Surakarta. This study employed research and development (R&D) approach. The preliminary study used qualitative and quantitativeresearch to describe the MPKKS factually. The steps ofdevelopment are conductedby initially designingthe conceptual model which has passed through expert validation by conducting focus group discussionsand resulting in the conceptual model. The model is then tested by experts through limited assessment to produce a model of development. This model isassessed for their effectiveness by practitioners to produce the final model. In conclusion, the development of competency-based model of MPKKS is effectively used in performance assessment to improve principals’competence of junior high school in Surakarta. Recommendation: the parties which concern on the performance assessment need to use MPKKS development, because it has been tested and proven to be very effective to improve the principals’performance based on their competence.